Standardy należytego uzasadnienia w świetle orzecznictwa Trybunału Konstytucyjnego i Europejskiego Trybunału Praw Człowieka: [Standards of proper judicial reasoning in the light of case-law of the [polish] Constitutional Tribunal and European Court of Human Rights] (Studia Prawnicze / The Legal Studies, 2014)
„Nasze czasy wiążą się z podwyższeniem wymagań i oczekiwań co do legitymizacji działania każdej władzy – a więc także władzy sądowej. Obecnie nie wystarcza oświadczenie: działam w granicach i na podstawie prawa, na podstawie mandatu prawa. Od władzy (...) oczekuje się, że będzie się legitymizowała transparencją, przezroczystością, uczytelnieniem swego działania wobec publiczności, nie tylko korzystając z udzielonej jej legitymacji w momencie powołania, ale także „legitymizując się” w codziennym działaniu.”Racją istnienia sądów i sędziów jest sprawowanie wymiaru sprawiedliwości. Wymiar ten następuje nie tylko poprzez wyroki sądowe i inne rozstrzygnięcia, ale także poprzez ich uzasadnienia.„Odpowiedzialny sędzia dąży (...) do pełnej akceptowalności jego orzeczeń nie tylko przez prawników, ale i obie strony procesu. Owa odpowiedzialność, brzemienna zarówno treścią moralną, jak i prawną, objawia się głównie w uzasadnieniach orzeczeń sędziowskich”, przy czym „każde uzasadnienie jest świadectwem umiejętności zawodowych i życiowych jego autora”. Uzasadnienie świadczy również o wewnętrznym poczuciu niezawisłości sędziego w sprawowaniu przez niego urzędu, jak również może wskazywać na to, na ile w wykonywaniu władzy sędziowskiej jest wewnątrzsterowny, a na ile zewnątrzsterowny, w jakim zakresie korzysta z powściągliwości sędziowskiej albo z sędziowskiego aktywizmu. The core function of the judiciary is the administration of justice through delivering judgments and other decisions. The crucial role for its acceptance and legitimization by not only lawyers, but also individulas (parties) and the hole society plays judicial reasoning. It should reflect on judge’s independence within the exercise of his office and show also judicial self-restraint or activism. The axiology and the standards of proper judicial reasoning are anchored both in constitutional and supranational law and case-law.Polish Constitutional Tribunal derives a duty to give reasoning from the right to a fair trial – right to be heard and bring own submissions before the court (Article 45 § 1 of the Constitution), the right to appeal against judgments and decisions made at first stage (Article 78), the rule of two stages of the court proceedings (Article 176) and rule of law clause (Article 2), that comprises inter alia right to due process of law and the rule of legitimate expactation / the protection of trust (Vertrauensschutz).European Court of Human Rights derives this duty to give reasons from the guarantees of the right to a fair trial enshrined in Article 6 § 1 of European Convention of Human Rights. In its case-law the ECtHR, taking into account the margin of appreciation concept, formulated a number of positive and negative requirements, that should be met in case of proper reasoning.The obligation for courts to give sufficient reasons for their decisions is also anchored in European Union law. European Court of Justice derives this duty from the right to fair trial enshrined in Articles 6 and 13 of the ECHR and Article 47 of the Charter of Fundamental Rights of the European Union.Standards of the courts reasoning developed by Polish constitutional court an the European courts (ECJ and ECtHR) are in fact convergent and coherent. National judges should take them into consideration in every case, to legitimize its outcome and enhance justice delivery.